Strategi Pengembangan Masyarakat Guna Mengoptimalisasi Potensi Agromaritim melalui Pembuatan Mineral Blok untuk Kambing di Desa Padaharja, Tegal - Binsar, Fernando Lukas; Rachman, Rizkhy Ananda Wida; Putri, Amanda Dwi; Khofifatuzzahro, Khofifatuzzahro; Ilhandi, Moch Gibran; Chan, Carey; Hidayat, Hafilah Rizka Nuha; Nurhayati, Nurhayati (Jurnal Pusat Inovasi Masyarakat, 2025)
Padaharja Village is one of the villages located in Kramat District, Tegal Regency with a strategic area location in developing agromaritime resources. One resource whose potential can be maximized is the livestock sector. Therefore, it is necessary to implement activities to support the results of the livestock sector so that they are maximized, one of which is mineral blocks. The aim of implementing mineral blocks for breeders, especially goats in Padaharja Village, is to maximize the mineral needs of goat livestock which often escape the attention of goat breeders. Activities are carried out offline with an approach in the form of socialization and demonstrating how to make mineral blocks. The results of this activity show a significant increase in farmers' understanding and skills regarding the use of mineral blocks. The impact of this activity is quite positive, with livestock farmers increasing their understanding of the importance of mineral nutrition for their livestock. The use of mineral blocks as a feed supplement has begun to be implemented by several breeders, and they report improvements in livestock health and productivity. Thus, the socialization and demonstration program for making mineral blocks in Padaharja Village has succeeded in increasing farmers' awareness and skills regarding the importance of mineral intake for livestock health and productivity.